Synthesis And Application Of Zno Nanorods For Oxygen Gas Sensor - Abd Wahid, Khairul Anuar (2015)
In this thesis, a high sensitivity and accurate gas sensor with operating temperature at room temperature has been successfully developed by using ZnO nanorods. A series of parametric studies via hydrothermal and PECVD have been carried out in order to synthesis a high dense and high aspect ratio of ZnO nanorods. It has been demonstrated that a high-density of ZnO nanorods with aspect ratio 15:1 can be successfully synthesized at an annealing temperature of 100oC and 3 hours growth duration for via hydrothermal. Meanwhile for PECVD, a high aspect ratio of 12:1 ZnO nanorods successfully synthesized at 4nm gold (Au) catalyst with chamber pressure of 700mTorr. SEM and AFM analyses showed that the formation of ZnO nanorods via hydrothermal is significantly influenced by the seeds particle morphology while for PECVD, the Au nanoparticle size and the proper ratio of vapors components are the major parameter affecting the ZnO nanorods growth. The grown ZnO from both samples is of the wurtzite crystal type based on raman shift E2(high) of 436cm-1.An electrical characteristics via four point probles been conducted and the results showed that the resistivity of the ZnO grown via hydrothermal and PECVD are 4.47×10−3Ω.